Peran Gender dalam Pemilihan Penolong Persalinan - Nurdin, Nurfadila; Saadong, Djuhadiah; Subriah, Subriah; Ningsi, Agustina (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2022)
Gender is the differences between men and women constructed socially and culturally related to roles, behaviors, and characteristics, which are considered appropriate for both and can be interchanged. The direct cause of maternal death is hemorrhage followed by hypertension in pregnancy and unassisted labor by health professionals. The study's aim is to determine the effect of gender roles in birth attendants elections at the Lancirang Health Center in Sidrap Regency. The research method is an analytic survey with a cross-sectional approach and sampling using purposive sampling of as many as 30 respondents. The Research was conducted in February – May 2021 using a data collection format. Analyzation using Multiple Linear Regression = 0.05. The results showed 18 (60%) mothers with gender roles in the 'good' category, 12 (40%) mothers with gender roles in the 'poor' category, 21 (70%) respondents chose the correct birth attendant, and there were 9 (30 %) respondents who chose the incorrect birth attendant. The statistical tests result has shown that gender roles influenced the selection of birth attendants with a P-value = 0.006. Thus can be concluded that gender roles affect the birth attendant election in the Lancirang Health Center Work Area, Sidrap Regency.